태양광 발전 연계 수전해 시스템의 경제성 분석 - 황순철(SUNCHEOL HWANG); 박진남(JIN-NAM PARK) (한국수소 및 신에너지학회 논문집, 2021)
Hydrogen production, hydrogen production cost, and utilization rate were calculated assuming four cases of hydrogen production system in combination of photovoltaic power generation (PV), water electrolysis system (WE), battery energy storage system (BESS), and power grid. In the case of using the PV and WE in direct connection, the smaller the capacity of the WE, the higher the capacity factor rate and the lower the hydrogen production cost. When PV and WE are directly connected, hydrogen production occurs intermittently according to time zones and seasons. In addition to the connection of PV and WE, if BESS and power grid connection are added, the capacity factor of WE can be 100%, and stable hydrogen production is possible. If BESS is additionally installed, hydrogen production cost increases due to increase in Capital Expenditures, and Operating Expenditure also increases slightly due to charging and discharging loss. Even in a hydrogen production system that connects PV and WE, linking with power grid is advantageous in terms of stable hydrogen production and improvement of capacity factor.